Lokuð fleiðrusýnataka með nál á Íslandi árin 1990-1999 - Jónas Geir Einarsson; Helgi J Ísaksson; Gunnar Guðmundsson (Læknafélag Íslands, Læknafélag Reykjavíkur, 2003)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn View/Open Objective: Closed pleural biopsy is done to determine causes of pleural effusion after fluid analysis has been nondiagnostic. The aim of the study was to evaluate results of closed pleural biopsy in Iceland. Material and methods: All pathology reports of closed pleural biopsy from 1990-1999 at the Department of Pathology were reviewed. Hospital records for these patients were screened. Results: There were 130 samples from 120 individuals. There were 74 males and 46 females. Deceased are 75/120. The most common diagnosis was pleuritis or fibrosis in 85/120, cancer in 15 and three had tuberculosis but 17/120 had other results. The sensitivity of a closed pleural biopsy for diagnosing cancer was 27%. Adding cytology increased the sensitivity to 56%. Of those that had pleuritis on initial biopsy the cause was found to be cancer in 33/85, pneumonia in 11, trauma in 5 and in 8 there were other causes. In 25/85 no etiology could be found. By doing further studies it was demonstrated that the cause for the fluid was malignancy in 55/120. Of those most had lung cancer or 24/55, and the second most common cause was breast cancer in 7. Despite further studies no cause was found in 32/85. Conclusions: Closed pleural biopsy has fairly low sensitivity for diagnosis of cancer but it can be increased by adding cytologic evaluation. It is necessary to do further investigations and follow-up in patients that have inflammation in pleural biopsy. Inngangur: Lokuð fleiðrusýnataka er gerð til að finna orsök fyrir vökvasöfnun í fleiðruholi sem ekki hefur fundist skýring á með vökvarannsókn eingöngu. Tilgangur rannsóknarinnar var að kanna niðurstöður lokaðrar fleiðrusýnatöku með nál á Íslandi. Efniviður og aðferðir: Hjá Rannsóknastofu Háskólans í meinafræði voru athuguð vefjarannsóknasvör allra fleiðrusýna frá 1990-1999. Sjúkraskýrslur voru kannaðar. Niðurstöður: Um var að ræða 130 sýni frá 120 einstaklingum, 74 körlum og 46 konum. ...